Tracheoesophageal fistula associated with bevacizumab after thoracic radiotherapy in non-small cell lung cancer: A case report. Issue 17 (April 2020) - Zhang, Tao; Yang, Yin; Cheng, Guowei; Chen, Ping; Bi, Nan
Abstract: Introduction: Tracheoesophageal Fistula (TF) is a rare complication of Bevacizumab. Thoracic radiotherapy may be a contributing factor to TF formation. To the best of our knowledge, we report the first case of Chinese patient with non-small cell lung cancer (NSCLC) who developed TF after completion of chemotherapy with bevacizumab and thoracic radiotherapy. Patient concerns: A 54-year-old male patient was diagnosed with NSCLC. He received definitive thoracic radiotherapy with concurrent pemetrexed and cisplatin chemotherapy. Two months after the treatment, the disease progressed with enlargement of right inguinal lymph node and chemotherapy of docetaxel, carboplatin and bevacizumab was administrated. Eighteen days after 4 cycles, the patient presented a sudden onset of acute cough after drinking. Diagnosis: Esophageal barium swallow revealed a TF. Gastroscopy confirmed a fistula in the esophagus. Interventions: A jejunal feeding tube was placed for nutrition for a month. After that a covered esophageal stent was placed in the esophagus. Outcomes: At the 6-month follow-up visit, the patient recovered well and had not developed any complication related to the stent placement. Conclusion: TF is a rare but life-threatening complication of bevacizumab. Careful observation is imperative for those patients who are administered bevacizumab, particularly in patients treated previously with thoracic radiotherapy.